Factors determining the economics of milk production in smallholder farms in Kenyahighlands. - Mwangi, A.C. (University of Nairobi, 1981)
Milk production from smallholder farms has gained inpo.us through various governmental policies. The -rost important measures that have been undertaken are the price incentives measures and creation of milk clera- w through school milk prograrrrfe. Cn the other hand, dairy products have become the nest inportant livestock commodities, both in terms of farm, income earnings end farm, family nutrition requirements. Mllk a3 a ma-i°r commodity has been experiencing seasonal fluctuations and insufficient supply. Weather basically contributes largely to the problem, but it is necessary to be able to quantify factors within the logical manipulation of the farmer inorder to be able to plan effectively. Data row small scale farms was subjected to production function and economic analyses to determine bottlenecks in milk production. A production model that explains the reality of milk production from small scale iarms was developed by comparing several known functions, ihe functions that were examined included linear, square, Cobb-Douglas and quadratic functions. The quadratic function was selected as the best fit. The model was used to determine the best operating conditions, points cf rL yield maxima per cow, and to determine attributes of milk production in smallholder farms. The findings cf the analyses revealed that there is a strong relationship between feeding concentrates and milk yield, and similarly, between farm produced by-products and milk yield. Gther attributes are the cow’s characteristic and environmental ^actors. The other research findings indicate that a majority oT the farms are within the profitable range. As to the consequences of increasing the hol'd sizes, the findings show diseconomies of herd sizes. The findings also sh the need for concerted effort between the biotechnicians and the economists in farm and national planning.L96